2015
DOI: 10.17576/jsm-2015-4410-01
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity, Fertility and Survival of Red Palm Weevil (Rhynchophorus ferrugineus) Larvae Reared on Sago Palm

Abstract: Red palm weevil (RPW),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…According to Quesada-Moraga et al [90], when adult males of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) were infected by inoculated adult females with dry conidia of the M. anisopliae isolate EAMa 01/58-Su, 100% mortality was obtained. Wai et al [91] concluded that mated female R. ferrugineus consume much of their energy during their reproductive cycle. Consequently, they remain with less potential to survive in comparison to virgin females.…”
Section: Discussionmentioning
confidence: 99%
“…According to Quesada-Moraga et al [90], when adult males of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) were infected by inoculated adult females with dry conidia of the M. anisopliae isolate EAMa 01/58-Su, 100% mortality was obtained. Wai et al [91] concluded that mated female R. ferrugineus consume much of their energy during their reproductive cycle. Consequently, they remain with less potential to survive in comparison to virgin females.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, RPW might reach up to the ninth instar depending on the food sources of their host plant ( Jaya et al 2000 , Ju et al 2011 ). In Malaysia, a study by Yong (2015) showed that the eggs took 4–5 d to hatch, larvae duration took about 120 d, pupal duration took 21–25 d, and the complete life cycle of the RPW took approximately 4 to 5 mo.…”
Section: Discussionmentioning
confidence: 99%
“…RPWs have four phases in their life cycle: eggs, larvae, pupae, and adults. Corresponding to several articles, the eggs deposited by adult female RPWs vary, ranging from 180 eggs to 396 eggs [ 33 , 34 , 35 , 36 , 37 ]. Depending on where the attack begins along the palm tree, adult females lay eggs in wounds or openings at the palm crown or leaf scar [ 35 ].…”
Section: Biology and Distribution Of R Ferrugineusmentioning
confidence: 99%
“…Corresponding to several articles, the eggs deposited by adult female RPWs vary, ranging from 180 eggs to 396 eggs [ 33 , 34 , 35 , 36 , 37 ]. Depending on where the attack begins along the palm tree, adult females lay eggs in wounds or openings at the palm crown or leaf scar [ 35 ]. The complete life cycle of the RPW varies from 45 days to 180 days [ 2 , 3 ].…”
Section: Biology and Distribution Of R Ferrugineusmentioning
confidence: 99%
See 1 more Smart Citation